2018
DOI: 10.1111/jipb.12602
|View full text |Cite
|
Sign up to set email alerts
|

Defective Kernel 39encodes a PPR protein required for seed development in maize

Abstract: RNA editing is a posttranscriptional process that is important in mitochondria and plastids of higher plants. All RNA editing-specific trans-factors reported so far belong to PLS-class of pentatricopeptide repeat (PPR) proteins. Here, we report the map-based cloning and molecular characterization of a defective kernel mutant dek39 in maize. Loss of Dek39 function leads to delayed embryogenesis and endosperm development, reduced kernel size, and seedling lethality. Dek39 encodes an E subclass PPR protein that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 66 publications
0
50
0
2
Order By: Relevance
“…PPR family proteins are present in most eukaryotes (Lurin et al 2004; Schmitz‐Linneweber and Small 2008), and this family is one of the largest protein families in plants, with most members localized to either the mitochondria or chloroplasts (Lurin et al 2004). Some PPR proteins are dual‐localized to the mitochondria and chloroplasts (Sosso et al 2012; Li et al 2018; Xiao et al 2018), and a few are targeted to the nucleus (Ding et al 2006), whereas SOAR1 is dual‐localized to the cytosol and nucleus (Jiang et al 2014). As we know, PNM1 is a PPR protein previously reported to localize to both the nucleus and mitochondria (Hammani et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PPR family proteins are present in most eukaryotes (Lurin et al 2004; Schmitz‐Linneweber and Small 2008), and this family is one of the largest protein families in plants, with most members localized to either the mitochondria or chloroplasts (Lurin et al 2004). Some PPR proteins are dual‐localized to the mitochondria and chloroplasts (Sosso et al 2012; Li et al 2018; Xiao et al 2018), and a few are targeted to the nucleus (Ding et al 2006), whereas SOAR1 is dual‐localized to the cytosol and nucleus (Jiang et al 2014). As we know, PNM1 is a PPR protein previously reported to localize to both the nucleus and mitochondria (Hammani et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, little or no functional redundancy among PPR proteins has been found in higher plants, this situation indicates that the functions of PPR proteins are highly diversified in these plants. Accumulating evidence has revealed that PPR proteins are involved in a wide range of biological processes, such as cytoplasmic male sterility (CMS; Gaborieau et al ., ; Igarashi et al ., ; Liu et al ., , ), embryogenesis (Cai et al ., ; Li et al ., ; Tadini et al ., ), retrograde signaling (Sun et al ., ), and low temperature stress (Wu et al ., ; Wang et al ., ). However, the molecular mechanisms underlying the roles of PPR proteins in low temperature stress remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has revealed that PPR proteins are involved in a wide range of biological processes, such as cytoplasmic male sterility (CMS; Gaborieau et al, *These authors contributed equally to this work. 2016; Igarashi et al, 2016;Liu et al, 2016Liu et al, , 2017, embryogenesis Li et al, 2018;Tadini et al, 2018), retrograde signaling (Sun et al, 2016), and low temperature stress (Wu et al, 2016b;Wang et al, 2017). However, the molecular mechanisms underlying the roles of PPR proteins in low temperature stress remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of cytological section was performed, as previously described (Li et al ). In brief, immature os1 mutant and wild‐type kernels were collected from the same segregating ears of 6 DAP.…”
Section: Methodsmentioning
confidence: 99%